Możliwości oddziaływania władz lokalnych na podnoszenie atrakcyjności inwestycyjnej gminy - Zakrzewska-Półtorak, Alicja (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
Local self-government authorities due to developing decentralization of local self-government, have wider possibilities to improve attractiveness of communes for sited and new potential investors. More and more often they manage very successfully in this field. Position of particular communes in terms of their investment attractiveness (thanks to owned sources) is not equal. So that some local authorities have to create new values the others - only underline owned ones. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1083, s. 253-260